Healthcare 4.0 and Health Management - YILIK, Pelin; BEYLİK, Umut (PEARSON JOURNAL, 2023)
Industry 4.0, which is rapidly developing and changing in today's world, has also heavily influenced the health sector and is gathered under Health 4.0. This study was conducted to discuss what Health 4.0 applications are and their importance in terms of health management within the scope of their contribution to health services and to make suggestions. In this context, Health 4.0 technologies and applications in the world and in Turkey are first explained. Subsequently, its importance in terms of Health Management was mentioned and suggestions were made. In terms of health management, it can be said that Health 4.0 primarily contributes to accessibility in health services, increases the comprehensiveness of health services, reduces health expenses, and is beneficial in terms of time and effectiveness in accurate diagnosis and treatment. In addition, it was emphasized that studies on the adaptation of health systems, health human resources and society to this rapid change are also important.